PENGARUH MODEL PEMBELAJARAN BRALANCING BERBANTUAN PERMAINAN MAGOAK-GOAKAN TERHADAP LITERASI SAINS SISWA KELAS IV SD N GUGUS II KECAMATAN BULELENG - Widiantini, Vina; I Made Ari Winangun; Ni Putu Candra Prastya Dewi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effect of implementing the Bralancing (Brain Balance Learning) model assisted by the traditional game Magoak-Goakan on the science literacy of fourth-grade elementary school students in Cluster II, Buleleng District. The type of research used is quasi-experimental with a Nonequivalent Control Group Design. The research population includes all fourth-grade elementary school students in Cluster II, Buleleng District. The sample was determined using a simple random sampling technique after an average equivalence test, resulting in SDN 2 Tukadmungga as the experimental group (21 students) taught using the Bralancing model assisted by Magoak-Goakan, and SDN 3 Tukadmungga as the control group (29 students) taught using conventional learning models. Data collection was carried out using a multiple-choice science literacy test. The test instrument was declared valid through content validity testing (Gregory) and item validity testing (point biserial). The data were statistically analyzed to test the hypothesis regarding the effect of the treatment on students' science literacy. The results are expected to provide empirical evidence regarding the effectiveness of integrating brain function balance models assisted by local wisdom in enhancing primary school students' science literacy.